Case Report: Severe hemophilia B patient with inhibitor and anaphylaxis reaction to FIX, successfully managed with concizumab prophylaxis therapy - Bonetti, Elisa; Esposto, Maria Pia; Zaccaron, Ada; Guardo, Chiara; Caddeo, Giulia; Chinello, Matteo; Balter, Rita; Pezzella, Vincenza; Vitale, Virginia; Cesaro, Simone (Frontiers in Pediatrics, 2025)
BackgroundHemophilia B is a rare X-linked disorder characterized by factor IX (FIX) deficiency, leading to spontaneous bleeding episodes predominantly affecting joints and muscles. Severe cases with FIX activity levels below 1% can develop inhibitors, rendering replacement therapy ineffective and posing additional challenges such as allergic or anaphylactic reactions to FIX infusions. Novel non-factor therapies, including concizumab, offer alternative strategies by targeting tissue factor pathway inhibitor (TFPI), a key regulator of coagulation. Concizumab restores thrombin generation and hemostasis, bypassing the need for FIX. Administered subcutaneously, it reduces treatment burden while enhancing adherence and quality of life.Case presentationWe report a pediatric case of severe hemophilia B with inhibitors and recurrent anaphylactic reactions to FIX therapy, and transitioned to concizumab therapy. Initial treatment included FIX replacement but repeated allergic reactions necessitated bypassing therapy such as recombinant activated factor VII (rFVIIa) and later concizumab. Following the initiation of concizumab, the patient experienced significant reductions in bleeding episodes, improved joint health scores, and decreased reliance on rFVIIa, with no hospitalizations or severe adverse events over four years.Discussion and conclusionThis case highlights concizumab's transformative role in managing hemophilia B with inhibitors, demonstrating its potential to address unmet clinical needs and improve outcomes, as corroborated by pivotal clinical trials. Comprehensive multidisciplinary care remains essential for optimizing long-term results.